Biodegradable Nanocapsules as siRNA Carriers for Mutant K‐Ras Gene Silencing of Human Pancreatic Carcinoma Cells. Issue 16 (20th February 2013) - Lin, Guimiao; Hu, Rui; Law, Wing‐Cheung; Chen, Chih‐Kuang; Wang, Yucheng; Li Chin, Hui; Nguyen, Quoc Toan; Lai, Cheng Kee; Yoon, Ho Sup; Wang, Xiaomei; Xu, Gaixia; Ye, Ling; et al.
Abstract The application of small interfering RNA (siRNA)‐based RNA interference (RNAi) for cancer gene therapy has attracted great attention. Gene therapy is a promising strategy for cancer treatment because it is relatively non‐invasive and has a higher therapeutic specificity than chemotherapy. However, without the use of safe and efficient carriers, siRNAs cannot effectively penetrate the cell membranes and RNAi is impeded. In this work, cationic poly(lactic acid) (CPLA)‐based degradable nanocapsules (NCs) are utilized as novel carriers of siRNA for effective gene silencing of pancreatic cancer cells. These CPLA‐NCs can readily form nanoplexes with K‐Ras siRNA and over 90% transfection efficiency is achieved using the nanoplexes. Cell viability studies show that the nanoparticles are highly biocompatible and non‐toxic, indicating that CPLA‐NC is a promising potential candidate for gene therapy in a clinical setting.